PENGARUH KNOWLEDGE MANAGEMENT TERHADAP KINERJA KARYAWAN MELALUI JOB DESCRIPTION PADA PT. BANK SULSELBAR KOTA MAKASSAR - Muharram Muharram; Andi Batary Citta; Mukhtar Galib (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2023)
This study aims to determine the effect of knowledge management on employee performance through job descriptions at PT. Bank Sulselbar Makassar. So the objectives to be achieved in this study are; 1). To find out and analyze the direct effect of knowledge management on job descriptions at PT. Bank Sulselbar Makassar, 2). To find out and analyze the direct effect of job descriptions on employee performance at PT. Bank Sulselbar Makassar, 3). To find out and analyze the indirect effect of knowledge management on employee performance through job descriptions at PT. Bank Sulselbar Makassar. The type of research data used in this study is the type of quantitative data, by means of data collection techniques namely; observation, questionnaires, and interviews. The sampling method used in this study was non-probability sampling - purposive sampling to obtain 61 samples or respondents. The data analysis technique used in this study is; validity and reliability test, and normality test as a prerequisite for the classical assumption test. And the data analysis method uses path analysis with the r test, t test and f test The results of this study indicate that: partially knowledge management and job description variables have a positive and significant effect on employee performance, and knowledge management has an effect on employee performance through job descriptions.